A Novel Shock Absorber with the Preload and Global Negative Stiffness for Effective Shock Isolation - Zecui Zeng; Lei Zhang; Ming Yan (Shock and Vibration)
A novel shock absorber with the preload structure and global negative stiffness is proposed for the shock isolation of sensitive systems. The novel shock absorber is composed of a linear spring and permanent magnet sets. The preload force and negative stiffness region are related to the attractive force between permanent magnet sets. The aim of this paper is to investigate the shock isolation performance of the novel shock absorber. Firstly, a static analysis of the novel shock absorber is carried out. Secondly, the motion stability of the NSA is analyzed by the Jacobian Matrix and the shock response is calculated numerically compared with the conventional preload structures. Finally, the shock test of the novel shock absorber is completed to verify the above results. It is found that the novel shock absorber could be advantageous in improving shock isolation in terms of relative displacement and absolute acceleration compared with conventional preload structures.